2021
DOI: 10.3390/su13063325
|View full text |Cite
|
Sign up to set email alerts
|

Karst Aquifer Vulnerability Assessment (KAVA) Method—A Novel GIS-Based Method for Deep Karst Aquifers

Abstract: Karst aquifers in the Dinaric karst are very rich with groundwater and are a very important resource for public water supply. The characteristics of the Dinaric karst are the lack, or very thin layer, of covering deposits, large amounts of precipitations, high groundwater velocities, very deep groundwater flow with a lot of faults and fault zones, pits to groundwater, concentrated sinking and large karst springs, making them extremely vulnerable to all anthropogenic influences, which are very quickly transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Dolines are readily identifiable areal features, and their locations are typically mapped for engineering and safety concerns and flooding hazards (Ford et al, 1997;Shofner et al, 2001;Angel et al, 2004). Doline density is variable and commonly used in models to assess aquifer vulnerability (Crawford and Veni, 1986;Ray et al, 1993;Doerfliger et al, 1999;Kochanov and Reese, 2003;Arthur et al, 2007;Biondić et al, 2021). It has been shown that high dolines density areas and strong fissuring corresponds to the areas with high and very high aquifer vulnerability (Moreno-Gómez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dolines are readily identifiable areal features, and their locations are typically mapped for engineering and safety concerns and flooding hazards (Ford et al, 1997;Shofner et al, 2001;Angel et al, 2004). Doline density is variable and commonly used in models to assess aquifer vulnerability (Crawford and Veni, 1986;Ray et al, 1993;Doerfliger et al, 1999;Kochanov and Reese, 2003;Arthur et al, 2007;Biondić et al, 2021). It has been shown that high dolines density areas and strong fissuring corresponds to the areas with high and very high aquifer vulnerability (Moreno-Gómez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Karst is one of the most outstanding landscapes in the world [22], concentrated in central and southern Europe, eastern North America, and eastern Asia, with an area of 22 million km2 [23,24]. The karst area of China accounts for more than 1/3 of the total land area, mainly concentrated in the South China Karst centered on the Guizhou Plateau, with an area of 550000 km2 [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to simplicity of use, semi-quantitativeindex-based methods-prevail. Most studies use a single groundwater vulnerability model (e.g., [9][10][11][12][13][14][15]), while those using two or multiple models are less common (e.g., [16][17][18][19][20]). Despite their widespread use, there are only a few groundwater vulnerability studies in Croatia, all of which are focused on karst aquifers, with the application of a single [12,15,21] or several groundwater vulnerability models [22].…”
Section: Introductionmentioning
confidence: 99%